2008
DOI: 10.1088/0031-9155/53/13/019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RF exposure in the head tissues of children and adults

Abstract: This paper analyzes the radio frequencies (RF) exposure in the head tissues of children using a cellular handset or RF sources (a dipole and a generic handset) at 900, 1800, 2100 and 2400 MHz. Based on magnetic resonance imaging, child head models have been developed. The maximum specific absorption rate (SAR) over 10 g in the head has been analyzed in seven child and six adult heterogeneous head models. The influence of the variability in the same age class is carried out using models based on a morphing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 39 publications
5
94
1
Order By: Relevance
“…Since local SAR 10g is more dependent on local geometry than the global average, these values are subject to greater uncertainty, especially when attempting to represent a population using a small number of models. It is difficult to assess this uncertainty; a 30% estimate is given in the mobile communications literature 28 (in the GHz range); however, the lower frequencies used in MRI will lead to deviations closer to 10% 29. Our own SAR 10g estimate for an adult model at 3 T was very close to the scanner's prediction (10.1 W kg −1 compared with 10 W kg −1 ), though this may be coincidental given that the model used by the scanner's own software is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since local SAR 10g is more dependent on local geometry than the global average, these values are subject to greater uncertainty, especially when attempting to represent a population using a small number of models. It is difficult to assess this uncertainty; a 30% estimate is given in the mobile communications literature 28 (in the GHz range); however, the lower frequencies used in MRI will lead to deviations closer to 10% 29. Our own SAR 10g estimate for an adult model at 3 T was very close to the scanner's prediction (10.1 W kg −1 compared with 10 W kg −1 ), though this may be coincidental given that the model used by the scanner's own software is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…When modeling specific absorption rates of RF to the womb of pregnant mothers, research suggests that exposures are likely low and not high enough to elevate the body temperature (26)(27)(28). But this modeling is based on numerous assumptions and extrapolations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have measured electromagnetic absorption in realistic child and adult head models that were developed based on medical images and compared this to absorption in the SAM phantom exposed to radiation from a mobile phone antenna [12,[16][17][18][19][20]. Some studies comparing the peak local SAR in the MRI-based head models from adults and children have found either no significant difference or a statistically higher peak SAR in the larger (adult) head [12,16,17].…”
Section: Head Size and Exposure Comparisonsmentioning
confidence: 99%
“…Wiart et al [18] reported that the peak 1-g SAR in the brain tissues of models of children aged between 8 and 15 years is comparable to that of adult models, while it is about two times higher for models of children aged between 5 and 8 years, due to the smaller thicknesses of the pinna, skin, and skull.…”
Section: Head Size and Exposure Comparisonsmentioning
confidence: 99%